2015
DOI: 10.1111/ijfs.12921
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and microbiological description of Caxiri – a cassava and corn alcoholic beverage

Abstract: Summary Caxiri is a fermented alcoholic beverage made from cassava, corn and sweet potatoes by indigenous people in Brazil. Saccharomyces cerevisiae Rhodotorula mucilaginosa, Lactobacillus fermentum, Bacillus subtilis and L. helveticus were the main microbial species detected. Maltose was the main carbohydrate found (19.12 g L−1), and lactic acid (15.09 g L−1) and ethanol (92.16 g L−1) were also found in high concentrations. Gas chromatography‐flame ionisation detector was used to identify thirteen volatile co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Lactic fermentation is the predominant type of fermentation reported for cassava products, but there are reports of the presence of other types of microorganisms at the beginning of the process [ 18 , 19 , 20 ]. As fermentation progresses, there is a succession of other microorganisms such as LAB, predominantly the genus Lactobacillus .…”
Section: Discussionmentioning
confidence: 99%
“…Lactic fermentation is the predominant type of fermentation reported for cassava products, but there are reports of the presence of other types of microorganisms at the beginning of the process [ 18 , 19 , 20 ]. As fermentation progresses, there is a succession of other microorganisms such as LAB, predominantly the genus Lactobacillus .…”
Section: Discussionmentioning
confidence: 99%
“…The maltose reaches values of 210 g/L at 0 hours, decreasing to values of 0.85 g/L at 120 hours. This is probably due to the microbial activity during the fermentation of the beverage, the glucose concentration varies from 6.04 to 0.38 g/L (Miguel et al, 2015). Like yakupa, chicha and cauim, lactic acid is the main metabolite in fermentation found, it is found in initial values of 4.59 g/L at 0 hours of fermentation, reaching values of 27.89 g/L at 120 hours (Faria-Oliveira et al, 2015).…”
Section: Presence and Role Of Microorganismsmentioning
confidence: 98%
“…Caxiri: It is a beverage made from cassava, corn and sweet potatoes, produced by the Juruna or Yudjá indigenous people in Brazil. Generally, it is associated with sacred rituals since it is prepared for consumption at parties and in collective work such as cutting down trees or cultivating fields (Miguel et al, 2015). Caxiri is obtained by fermenting the roots of purple cassava for two days in running water in order to soften the bark.…”
Section: Brazilmentioning
confidence: 99%
“…Other authors ( Miguel et al, 2015 ) studied the microbial diversity present in a non-commercial caxiri prepared with cassava, maize and sweet potatoes. They found that S. cerevisiae was also the dominant yeast during the entire process, but LAB were the dominant bacteria, with L. fermentum and Lactobacillus helveticus being the dominant species, unlike what was found by Santos et al (2012) where the Bacillus genus was dominant.…”
Section: Fermented Beveragesmentioning
confidence: 99%
“…LAB were the principal microorganisms present at the end of the fermentation process. Fermented foods (A) Caxiri (Miguel et al, 2015), (B) Taruba (Ramos et al, 2015), (C) Beijus (Google, license-free), (D) Maize chicha (Google, licensefree), and (E) Llama charqui (Google, License free).…”
Section: Cottonseed and Rice Beveragementioning
confidence: 99%